Why has model‐informed precision dosing not yet become common clinical reality? lessons from the past and a roadmap for the future. Issue 5 (4th April 2017) - Darwich, AS; Ogungbenro, K; Vinks, AA; Powell, JR; Reny, J‐L; Marsousi, N; Daali, Y; Fairman, D; Cook, J; Lesko, LJ; McCune, JS; Knibbe, CAJ; et al.
Abstract : Patient groups prone to polypharmacy and special subpopulations are susceptible to suboptimal treatment. Refined dosing in special populations is imperative to improve therapeutic response and/or lowering the risk of toxicity. Model‐informed precision dosing (MIPD) may improve treatment outcomes by achieving the optimal dose for an individual patient. There is, however, relatively little published evidence of large‐scale utility and impact of MIPD, where it is often implemented as local collaborative efforts between academia and healthcare. This article highlights some successful applications of bringing MIPD to clinical care and proposes strategies for wider integration in healthcare. Considerations are brought up herein that will need addressing to see MIPD become "widespread clinical practice, " among those, wider interdisciplinary collaborations and the necessity for further evidence‐based efficacy and cost–benefit analysis of MIPD in healthcare. The implications of MIPD on regulatory policies and pharmaceutical development are also discussed as part of the roadmap.